‘They treat us like machines’: migrant workers’ conceptual framework of labour exploitation for health research and policy - Mary Alison Durand; Cono Ariti; Sabah Boufkhed; Nicki Thorogood (BMJ Global Health)
Background The exploitation of migrant workers ranks high on global political agendas including the Sustainable Development Goals. Research on exploited workers, using assessment tools where exploitation is defined by professional experts, indicates serious health concerns and needs. Yet, migrant workers are rarely asked about their understanding of a phenomenon they may experience. Our study aimed to conceptualise ‘labour exploitation’ from the perspective of migrant workers employed in manual low-skilled jobs.Methods Twenty-seven Latin Americans working in London (UK) participated in Group Concept Mapping; a participatory mixed-method where qualitative data are collected to define a concept’s content and then analysed using quantitative methods to generate a structured conceptual framework. Participants generated statements describing the concept content during brainstorming sessions, and structured them during sorting-rating exercises. Multi-Dimensional Scaling and Cluster Analysis were performed, generating a conceptual framework that clarified the dimensions, subdimensions and constituent statements of the concept of labour exploitation from migrant workers’ perspectives.Results Three key dimensions were identified: ‘poor employment conditions and lack of protection’, covering contractual arrangements and employment relations; ‘disposability and abuse of power’ (or ‘dehumanisation’) covering mechanisms or means which make migrant workers feel disposable and abused; and ‘health and safety and psychosocial hazards’ encompassing issues from physical and psychosocial hazards to a lack of health and social protection. ‘Dehumanisation’ has not been included in mainstream tools assessing exploitation, despite its importance for study participants who also described harsh situations at work including sexual, physical and verbal abuse.Conclusion Our study provides a conceptual framework of labour exploitation that gives voice to migrant workers and can be operationalised into a measure of migrant labour exploitation. It also calls for the dimension ‘dehumanisation’ and structural forms of coercion to be integrated into mainstream conceptualisations, and their workplace hazards to be urgently addressed.